Islamic economic perspective on poverty level: determination of economic growth, unemployment levels, and minimum wages in Lampung province / Ismi Sari, Heni Noviarita and Yulistia Devi - Sari, Ismi; Noviarita, Heni; Devi, Yulistia (Universiti Teknologi Mara Selangor, 2023)
The problem of poverty is one of the problems in the economic development of each region, be it a regency or province. The success of Lampung Province in overcoming poverty has not been fully successful, because basically poverty will continue to increase from last year to the following year. As economic growth increases, it is undeniable that poverty will decrease. The unemployment rate in Lampung Province has fluctuated so this has an impact on poverty because it is difficult for workers to get jobs which causes increased unemployment. And the minimum wage has increased, but this has not been able to reduce the poverty rate. The method used in this research is a quantitative method. The data analysis used was multiple linear regression which was processed using EViews 10. The data obtained is secondary data from the Central Bureau of Statistics of Lampung Province. This study aims to determine the effect of economic growth, the open unemployment rate, and the minimum wage on the poverty rate in the District/City of Lampung Province. The results of this study indicate that simultaneously economic growth, the open unemployment rate, and the minimum wage have a significant effect on the poverty rate. Partially, economic growth does not affect the poverty rate, the open unemployment rate has a significant effect on the poverty level and the minimum wage has a significant effect on the poverty level. From the perspective of Islamic economics, the poverty that occurs in Lampung Province in economic activities, the government must apply the principles of Islamic economics. The existence of Islamic economic principles is one of the solutions to the problem of poverty in Lampung Province.